Relicts of Paleoproterozoic LIPs in the Belomorian province, eastern Fennoscandian Shield: barcode reconstruction for a deeply eroded collisional orogen - Alexandra Stepanova; Vladimir S. Stepanov; Alexander N. Larionov; Ekaterina B. Salnikova; Alexander V. Samsonov; Pavel Azimov; Svetlana V. Egorova; Irina I. Babarina; Yulia O. Larionova; Maria A. Sukhanova; Anna V. Kervinen; Oleg A. Marksimov (2021)
Table S1. Data on chemical composition of Paleoproterozoic mafic dykes and 20 intrusions in the Belomorian Province